2007
DOI: 10.1139/y07-088
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of antioxidative status, lipid peroxidation, and lipid profile in insulin-dependent and non-insulin-dependent diabetic patients

Abstract: This study aimed to investigate the interrelationship of plasma lipid profile, lipid peroxidation, and erythrocyte antioxidative defense in patients with insulin-dependent (IDDM) and non-insulin-dependent (NIDDM) diabetes mellitus. Plasma levels of total cholesterol, triglycerides, and lipid peroxides and the activities of copper, zinc superoxide dismutase (CuZnSOD), catalase, glutathione peroxidase (GSH-Px), as well as the amount of glutathione in erythrocytes, were determined in IDDM, NIDDM, and nondiabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…It has been shown in various studies that diabetes mellitus is associated with increased formation of free radicals, and heavy oxidative stress [3]. This is supported by data showing that supplementation with nonenzymatic antioxidants, such as vitamin E and vitamin C, diminished diabetes-induced increase in lipid peroxidation (MDA) in many rat tissues, including kidney, liver, and muscles, as well as in plasma and erythrocytes [40,41]. Furthermore, a reduction in action of GSH level, GSH-Px, SOD, and CAT, involved in the detoxification of H 2 O 2 , has been observed in diabetic rats and humans [41].…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown in various studies that diabetes mellitus is associated with increased formation of free radicals, and heavy oxidative stress [3]. This is supported by data showing that supplementation with nonenzymatic antioxidants, such as vitamin E and vitamin C, diminished diabetes-induced increase in lipid peroxidation (MDA) in many rat tissues, including kidney, liver, and muscles, as well as in plasma and erythrocytes [40,41]. Furthermore, a reduction in action of GSH level, GSH-Px, SOD, and CAT, involved in the detoxification of H 2 O 2 , has been observed in diabetic rats and humans [41].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the findings of this study, there are reports that have identified an increased SOD level in human diabetics, highlighting the complex interplay of patient, disease, and the multitude of parameters that combine to result in oxidative stress. 20 Consumption of Purina DM diet for 8 weeks resulted in a significant increase in GPx activity in both diabetic and control cats. One potential explanation for the apparent effect of diet on GPx levels would be the presence of selenium in the diet used in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Constant exposure to free radicals and high oxidative stress in diabetes have also been associated with erythrocyte structural damage. [ 18 ] Lipid peroxidation alters the cellular structure of membrane-bound enzymes by changing phospholipids and fatty acid composition. Previous studies have reported reduced erythrocyte ATPase activity, specifically the Na + /K + ATPase in insulin-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%